77 A virtual reality: using simulation and virtual teaching tools to create an equitable induction experience for new trainees. (30th November 2020) - Thomas, Rhian; Tadros, Shereen; Rosser, Elisabeth; Sloper, Emily; Jones, Rachel; Carley, Helena; Murray, Alexandra; Tatton-Brown, Kate; Chigaru, Linda
Abstract : Background: Clinical genetics is a small specialty with around 70 trainees nationally. New trainees traditionally have a period of observing clinics led by consultants and experienced genetic counsellors before leading their own clinic. This is an important time in which they learn practical and communication skills with respect to approaching a consultation, however, the experience can be variable dependent on the centre. In light of the coronavirus pandemic, knowing that many new trainees would not be able to access this vital induction period, we devised a virtual induction programme. Methods: A group of clinical geneticists from three UK centres, including GOSH, worked in collaboration with the GOSH Clinical Simulation Team to devise and deliver a programme that would be accessible to all new trainees. Important topics for discussion were agreed; example consultations were filmed, with the help of actors; and trainee simulations were planned. Results: The virtual induction runs live over two days, with homework, in the form of the filmed consultations that can be accessed at any time. The first day has been completed, delivering training to around 20 new trainees. The feedback we have received from both trainees and training programme directors has been overwhelmingly positive. Discussion: Given the ongoing impact of the coronavirus pandemic, creative ways of delivering training are flourishing. We have created a bank of videos and presentations, as well as a template for future induction sessions, ensuring a basic level of equity between trainees at different genetics centres. Conclusion: Virtual induction tools are a valuable and vital addition to new trainee induction to ensure equity of training, both during the current pandemic and beyond. This approach would work very well on a national level for other small specialties; or on a regional or local level for larger specialties.